2005
DOI: 10.1108/09590550510581458
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and age differences in online buying

Abstract: PurposeThis paper examines the shopping and buying behavior of younger and older online shoppers as mediated by their attitudes toward internet shopping.Design/methodology/approachOver 300 students and staff from a US university completed a survey regarding their online shopping and buying experiences for 17 products.FindingsThe results show that, while older online shoppers search for significantly fewer products than their younger counterparts, they actually purchase as much as younger consumers. Attitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
174
4
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(194 citation statements)
references
References 10 publications
(18 reference statements)
11
174
4
5
Order By: Relevance
“…The older generation is not comfortable with Internet, thus they avoid online insurance Web sites. Our research supports the research of Sorce et al , 69 which states that older customers have to be enticed to use Internet. They do not know what to expect from the online Web sites, thus for them the alternatives are few and may fi nd the physical presence of the insurance agents more assuring than the ' virtual entity ' of insurance fi rm.…”
Section: Findings and Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The older generation is not comfortable with Internet, thus they avoid online insurance Web sites. Our research supports the research of Sorce et al , 69 which states that older customers have to be enticed to use Internet. They do not know what to expect from the online Web sites, thus for them the alternatives are few and may fi nd the physical presence of the insurance agents more assuring than the ' virtual entity ' of insurance fi rm.…”
Section: Findings and Discussionsupporting
confidence: 79%
“…68 The older customers do not feel comfortable with online insurance services and may have to be motivated to try out online services. 69 This result in two more hypotheses that we intend to test:…”
Section: Service Attributesmentioning
confidence: 99%
“…They provided empirical evidence of the concepts put forward by Tauber [43] and Hirschman and Holbrook [44]. While utilitarian values such as convenience [1,19,38,[46][47][48] and price [28,49] have a rational dimension, hedonistic values such as enjoyment and entertainment [28,38,44,47,50] are of a more affective nature. Nevertheless, these values can be applied to online shopping experiences that provide the hedonic values of enjoyment and fun via users' interactions with the online store.…”
Section: Methodsmentioning
confidence: 99%
“…Indicatively, in the context of web retailing, Vijayasarathy [75] reported that users' general acceptance of the internet affected their shopping behavior accordingly. Similarly, Farag et al [21] and Sorce et al [66] showed that demographics play an important role in the shopping adoption process, while Vrechopoulos et al [78] found significant differences between VWs' retail store selection criteria in terms of the importance consumers attach to them.…”
Section: Research Hypotheses Formulationmentioning
confidence: 99%